Raising Indonesian EFL Learners’ Intercultural Awareness through Asian Folktales-Mediated Tasks - Salika Nahja Hidayah; Fachri Ali (EDULANGUE, 2023)
Evolving learners’ intercultural awareness (ICA) has been one of the goals for 21st century learning competencies. Nevertheless, ICA has not been commonly developed through Asian folktales. To fill this void, the present action research aims to showcase a practical insight into the teaching by the adoption of folktales to raise Indonesian EFL learners’ intercultural awareness. Eleven students joined an EFL learning center in Pekalongan, Indonesia were recruited to participate. Data were garnered through classroom observation and semi-structured interview. The data were analyzed employing a thematic analysis. Framed in Yuanhua and Ying’s (2015) intercultural awareness fundamentals, study findings demonstrate that the students viewed cultural aspects from what they experienced, embedded cultural resources, such as symbols, languages, norms, values, and rituals in learning process, promoted self-regulated learning in intercultural communication, engaged in interpreting and comparing cultural contents among Asian folktales, and communicated cultural resources in their daily lives. This study concludes with some empirical and practical implications for how folktales are incorporated into teaching to foster EFL learners’ intercultural awareness